Antiinflammatory Activity Test of Aqueous Extracts Herb of Ciplukan (Physalis angulata L.) in Caragenan Inducted Wistar Rat (Rattus norvegicus L.) - Sri Luliana; Ressi Susanti; Ellya Agustina (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Ciplukan (Physalis angulata L.) empirically has been used to treat sore throat, inflammatory of the airways, gingivitis, and other diseases. This research was to determine the inflammatory activity of water herb extract of P. angulata L. on white male rats edema Wistar strain induced carragenan. P. angulata L. herbs were extracted using infundation method and were dried with frezee drying. Parameter that would be observed of this research was the inhibition foot edema of rat after induction of 0.1 mL of λ-carragenan 2% for 360 minutes. Measurement of edema volume was using pletismometer. The results of this research showed water herb extract of P. angulata L. in dose 100, 200, and 400 mg/kgBW has potensial as an antiinflammatory drug by percent respectively were 20.13; 28.93; and 34.70%. The three doses hasn’t showed any significant difference (p>0.05) with the positive control of diclofenac sodium dose 4.5 mg/kgBW was 33.90%. Conclusion of this research states water herb extract of P. angulata L. has antiinflammatory activity with effective dose of 400 mg/kgBW.